Can Tourists Experience Emotional Solidarity with Residents? Testing Durkheim's Model from a New Perspective. (July 2013) - Woosnam, Kyle M.; Aleshinloye, Kayode Dare
In the context of resident and tourist relationships in a destination, perspectives of the former are rarely considered. This is likely a function of the continued attention paid to studies focusing on the former in addressing sociocultural impacts of tourism. This work examines the relationship as perceived by tourists, utilizing the theoretical framework of emotional solidarity. Confirmatory factor analysis was used to examine the factor structure of the four constructs (i.e., shared beliefs, shared behavior, interaction, and emotional solidarity) within Durkheim's model. This works shows continued support for the framework with each of the antecedent constructs significantly predicting emotional solidarity, explaining approximately 55% of the variance in the construct. Implications and limitations of the work along with future research opportunities are discussed.